Genotypic and Phenotypic Assessment of Hyaluronidase among Type Strains of a Select Group of Staphylococcal Species - Mark E. Hart; Morgan J. Hart; Anna J. Roop (International Journal of Microbiology)
Hyaluronidases degrade hyaluronic acid, a major polysaccharide of the extracellular matrix of tissues, and are considered important for virulence in a number of Gram-positive and -negative bacteria. The purpose of the present study was to determine the prevalence of hyaluronidase among clinical strains of Staphylococcus aureus and among other Staphylococcus species. Spent media and chromosomal DNA were assessed for hyaluronidase activity and the absence or presence of a hyaluronidase gene (hysA) by Southern analysis, respectively. All S. aureus strains examined exhibited at least one hybridizing band (half of the strains exhibited two or more hybridizing bands) when probed for hysA and all but three of these strains produced hyaluronidase. In contrast, none of the type strains of 19 other species exhibited either hyaluronidase activity or hybridizing bands when probed for hysA. These data support the hypothesis that among members of the Staphylococcus genus only strains of S. aureus possess the enzyme hyaluronidase. This would suggest that hyaluronidase represents yet another potential virulence factor employed by S. aureus to cause disease and may represent a diagnostically important characteristic for distinguishing S. aureus from other members of this genus.